From 'Matie' to citizen - graduate attributes as signature learning at Stellenbosch University. - Jacobs, Cecilia; Strydom, Sonja (The IIE, 2014)
Graduateness is generally understood to mean the generic qualities that might be expected of any graduate. The issue of graduateness is explored in this article through an initiative at Stellenbosch University which took the form of a Signature Learning Experience (SLE) entitled: ‘Being a Matie, being a citizen’. This initiative was designed as a common learning experience for first-year students through which the graduate attributes could be embedded. The article draws on Barrie’s research into graduate attributes, to analyse the development and implementation of the initiative. The article maps the SLE initiative against Barrie’s conceptualisations of how graduate attributes are understood by academics, as well as understandings of how students acquire generic graduate attributes. Multi-method approaches were used to gather data about the initiative, which was piloted as a semester-long programme in the co-curriculum, with a group of first-year students. The themes emerging from the findings relate to the competing demands of the formal and co-curriculum and the challenges of embedding graduate attributes in the curriculum. The conclusions point to the need for a broader conversation around approaches towards embedding graduate attributes.
Keywords: Signature learning; Learning experience; Graduate attributes